Volatility spillovers in the Iberian electricity market - Vicente, João (2018)
With the globalization of the world economy, the relationships between commodities, financial and other markets are relevant. Although the electricity market is a more recent kind of market, it is still related with other markets, such as, commodities markets (natural gas, coal, oil), and carbon emissions markets. In this work, we propose to study the interconnections between the day-ahead Iberian electricity market (MIBEL) and the commodities markets, as well as, the carbon emissions markets between 2010 and 2016. To achieve this purpose, we use the Diebold-Yilmaz framework, which proposes measures of the interdependence of returns and volatilities through variance decomposition of forecasted error variances in a generalized vector autoregressive model. Results show that the markets that had a higher influence in MIBEL in the analyzed period were the TTF and Zeebrugge natural gas markets and the markets that MIBEL most influenced were the Coal (API2) and CER market.